TYPES OF SUTURING AND THEIR CLINICAL OUTCOME IN OPERATED PATIENTS IN A RURAL TERTIARY CARE SETUP - Tomar, Janvi; MH, Shaikh; Shah, Aashay (International Journal of Clinical and Biomedical Research, 2017)
Introduction: The present study was aimed at different modalities of abdominal skin suturing techniques and their outcome in various abdominal skin incisions. Material and methods: All the patients above the age of 18 years irrespective of gender who were undergoing abdominal surgeries and getting sutured by either Simple, mattress, subcuticular or tension sutures were included in the study. The demography, diagnosis, type of wound & suture and its outcome was followed till day 14. Results: A total of 120 randomly selected cases with different abdominal incisions and different suturing techniques associated with co-morbid factors were selected. Majority of cases i.e, 40 (33.3%) belonged to inguinal hernia, followed by appendicitis, intestinal perforation, intestinal obstruction. Age of 61 to 70 was the most common age group. Most of the cases had clean wound (59) followed by clean contaminated (27) and contaminated wounds (28). The types of sutures observed were simple, mattress, subcuticular and tension, which were done in 30, 24, 30 and 31 patients respectively. Among these the least complications were seen with subcuticular followed by simple type of sutures. The groups of the types of suture used were not comparable due to difference in the type of wound and disease in the patients. Conclusion: Although every type of suture has its own advantages, disadvantage, indications and contraindications, simple and subcuticular sutures have better outcome as compared to other forms of suture. Key words: Abdominal incisions, Clinical outcomes, Suturing techniques.